Transcatheter Coil Embolization of a Coronary Artery-Left Ventricular Fistula Associated with Single Coronary Artery Anomaly - Ozlem Ozcan Celebi; Alper Canbay; Erdem Diker; Barbaros Çil; Kudret Aytemir; Ali Oto (Case Reports in Vascular Medicine)
Single coronary artery anomaly associated with coronary fistula is a rare entity. Transcatheter coil embolization is the treatment of choice for coronary artery fistulas. In this case report, we describe a patient with both single coronary artery anomaly and coronary fistula who was successfully treated with coil embolization.